A review of electroplating for V–VI thermoelectric films: from synthesis to device integration. Issue 17 (11th September 2015) - Rostek, Raimar; Stein, Nicolas; Boulanger, Clotilde
Abstract: Abstract : Starting with the first published works on the electrochemical deposition of thermoelectric (TE) V–VI compounds in the early nineties, these past two decades have seen a steady increase in scientific interest and publications on this topic. This is hardly surprising, as TE devices offer unique opportunities for power generation in virtually any environment ("energy harvesting") or demanding cooling applications through the Peltier effect. This review first provides an overview of the advances in the electrodeposition of n- and p-type thin films based on Bi2 (Te, Se)3 and (Bi, Sb)2 Te3, the currently best-known TE materials for room temperature applications. The overview includes information about the electrolyte and the deposition conditions as well as the achieved composition, thickness, morphology, and TE properties of the deposited films. Additionally, we present the state-of-the-art and recent developments in electroplating-based fabrication processes for microscale TE devices.